Journal of Human Sport and Exercise - 2021 - Autumn Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc2.42
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differences according to gender in the level of physical activity, motivation, psychological needs and responsibility in Primary Education

Abstract: The objective of the study was to verify the differences according to gender in the levels of physical activity, motivation, basic psychological needs satisfaction and responsibility in students of 5th and 6th grade of Primary Education (M = 10.51, SD = .53). In total, 68 students answered a series of questionnaires evaluating the intention to be physically active, motivation, the satisfaction of basic psychological needs, and the levels of personal and social responsibility. These subjects also wore an accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Finally, the third objective sought to observe whether there were differences in the levels of responsibility depending on the age and gender of the participants. This was an objective whose hypothesis was not entirely clear, given that there are studies that observe differences according to gender in the values of responsibility, with higher values in boys [ 32 ] and others in girls [ 31 ], while others fail to identify such differences [ 63 ]. The same occurs with age, where research is observed that identifies higher values of responsibility in younger students [ 32 ] and others in older ones [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the third objective sought to observe whether there were differences in the levels of responsibility depending on the age and gender of the participants. This was an objective whose hypothesis was not entirely clear, given that there are studies that observe differences according to gender in the values of responsibility, with higher values in boys [ 32 ] and others in girls [ 31 ], while others fail to identify such differences [ 63 ]. The same occurs with age, where research is observed that identifies higher values of responsibility in younger students [ 32 ] and others in older ones [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a fundamental aspect is to observe whether there are differences depending on the age and gender of the participants in the profiles carried out, given that in the bibliography cited, the results are not entirely illuminating in this respect and neither with regard to educational level. Studies can be found indicating higher levels of responsibility in girls [ 31 ] and others in boys [ 32 ], while others claim the opposite [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to examine the motivational profile of adolescent students, as well as its link with responsibility, basic psychological needs and classroom social climate, and to review gender differences. The satisfaction of students' basic psychological needs is reflected in more self-determined levels of motivation that generate behaviours based on personal and social responsibility (Manzano-Sánchez et al, 2021). Thus, a classroom social climate focused on the teaching-learning process of students favours the acquisition of knowledge (Cid et al, 2019), promotes the development of personal skills (Alevriadou & Pavlidou, 2016;Hidalgo-Rasmusen et al, 2013), generates a greater intention to practice physical activity (Taylor et al, 2010) and reinforces young students' social satisfaction in the classroom (Baena-Extremera et al, 2013;Garn et al, 2014;Vallerand, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the variables of responsibility and classroom or school social climate, a positive and significant association of responsibility with school social climate, basic psychological needs (autonomy, competence and relatedness), the self-determination index and prosocial behaviour was observed (Manzano- Sánchez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation